ATLANTIS IN SPAIN IV - Papamarinopoulos, S.P (Bulletin of the Geological Society of Greece, 2010)
Many analysts in the past faced Atlantis’ main city with the same way they faced his idealised concentric cities which he described in his dialogues. However, Atlantis’ concentric city has a marked difference which is recognisable if the analyst has geological knowledge. For instance the concentric scheme, the geothermal springs and the black, white and red rocks correspond in volcanogenic, impactogenic and diapeirogenic craters. It is known that building material from rocks existing in the vicinity of the two first, from the three, types of craters have been used in the past. It is also known that cities have been developed both on volcanogenic craters such as Santorin in the Aegean Sea, or on impactogenic craters such as in Nordlichen in Germany and in Yemen’s capitol respectively. A simulation experiment was carried out exactly in the platonic geomorphological conditions assuming that the concentric scheme could be of impactogenic origin. The result showed that such multi-ringed crater exhibits the platonic characteristics presented in Critias. However, such solution is not unique because the other two types of craters have not been tested yet. The statistical criterion which may be applied in all three simulations in the described platonic environment will decide by itself which is the most optimal solution between all three. Many experts who know nothing about Plato’s views about science and mythology can not differentiate between genuine and fabricated myths utilised by Plato. Most of them do not understand that the multiringed crater called Atlantis too by Plato is revealed in the ancient myths prior to Plato and was placed by these writers West of the Gibraltar Straits. Philostratus, in Roman times, is the only Greek writer who described its geological nature in detail and presented its position in Southern Spain. That crater Geryonis was associated with Heracles’ visit in Iberia. In the latter’s sea environment there are several submerged gigantic diapeirogenic craters and a small one visible even today in Andalucía’s. The geological age of the submerged craters, in Cadiz, precedes the prehistoric Greeks’ and Iberians’ presence in the area. One of them possibly became the object of observations of prehistoric Greek mariners who passed Heracles’ Pillars and it was interpreted as Poseidon’s act. These Greek mariners were accustomed to interpret craters in the Aegean Sea such the Nisyros’, for instance, one as Poseidon’s act too.